Assessment of Survivability of Vitrified Embryos Depending on the Stage of Development - O.V. Shurigina1, S.Z. Yuldasheva2, O.V. Ivanova3, N.N. Demidova4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Freezing embryos of excellent and good quality allows you to maintain reproductive potential for patientsin the future and achieve pregnancy using one stimulation cycle. Cryopreservation of embryos can becarried out at any stage of development. Vitrification as a method of cryopreservation combines the use ofhighly concentrated solutions of cryoprotectants and rapid (almost instantaneous) cooling by immersingsamples directly in liquid nitrogen. Due to this, the main goal of vitrification is achieved - the absence of theformation of ice crystals, which can damage the cell structure. The advantages of vitrification are as follows:a high concentration of cryoprotectants and a high cooling/thawing rate eliminate the damage caused by theformation of intracellular ice, as well as the undesirable osmotic effects of dehydration and rehydration dueto extracellular crystal formation.